1990
DOI: 10.1002/food.19900340418
|View full text |Cite
|
Sign up to set email alerts
|

Tension of oil‐water interface and properties of O/W emulsions in dependence of faba bean globulins

Abstract: Compared with faba bean globulin the improved flow, gelifying, surface and emulsifying properties of aqueous solution of the corresponding acetylated derivatives are reflected in O/W emulsions by their enhanced stability.Investigations were made concerning the changes of the flow, gelifying [l], surface [2] and emulsifying [2,3] behaviour of aqueous faba bean globulin solutions dependent on their acetylation degree and the rheological properties of O/W emulsions stabilized by acetylated faba bean globulins [4]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…This is in accordance with results of previous studies on faba bean protein isolates [7,8,9, 241 where a decreasing droplet size and increasing centrifugal stability with progressive acetylation was found.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…This is in accordance with results of previous studies on faba bean protein isolates [7,8,9, 241 where a decreasing droplet size and increasing centrifugal stability with progressive acetylation was found.…”
Section: Discussionsupporting
confidence: 95%
“…The calculated CAC suggests that the affinity of FBPI to the air/water interface significantly increases with acetylation, whereas the dependence of the equilibrium surface pressure on the degree of blockage is not significant. Thus, it is possible to explain previous results on faba bean isolates which showed largely improved emulsifying properties by acetylation but with no [9] or only small measurable differences 181 in the adsorption behaviour. One reason [ S ] , the dissociation seems to proceed more completely up to the protein subunit (about 60 m a ) .…”
Section: Discussionmentioning
confidence: 79%
“…Acetylation increased the flow, gelifying, surface and emulsifying properties, as well as the physical stability. (Schmandke et al, 1990) Chemical FBPIs were obtained by aqueous extraction at pH 7.5 followed by isoelectric precipitation from faba bean flours. Acetylation was in combination with methoxy pectin.…”
Section: Methodsmentioning
confidence: 99%
“…In the early 1990s, chemical modification focused on acetylation of FBPIs. Schmandke et al (1990) compared the emulsifying properties of unmodified and acetylated FBPI (degree ~97%); they found that acetylation improved the flow, gelifying, surface and emulsifying properties, as well as the physical stability of emulsions. This group later examined the association of low methoxylated pectin and acetylated FBPI as emulsifiers in O/W emulsions.…”
Section: Chemical Modificationsmentioning
confidence: 99%